Reading the Context: Family Reading Experiences in a Honduran Community - Aguilar Domínguez, Ligia María (2022)
Children's literature books in the Honduran context are scarce, foreign, and are unrelated to families’ daily life, additionally they are not always an available resource at home. This situation limits the literacy context of families with low socioeconomic status. This study explores the meanings that ten families with preschool children in the Villanueva neighborhood of Tegucigalpa, Honduras, give to the contextualized children's literature books created for this purpose and their reading experiences with this resource. Contextualized children's literature is defined as literature whose text and images illustrate the local context of the community to be studied. In this qualitative phenomenological design, direct observation of reading sessions was used for data collection. Semi-structured interviews were also conducted with the same sample of families. The data collected were analyzed through the interpretative phenomenological model with the assistance of MAXQDA. Contextualized children's literature proved to be a medium that enriches the literacy context, because it motivates adult readers and pre-school children to participate in reading activities and to talk about their social reality, that is why its use is recommended.